ARCII: A phase II trial of the HIV protease inhibitor Nelfinavir in combination with chemoradiation for locally advanced inoperable pancreatic cancer. Issue 2 (May 2016) - Wilson, James M.; Fokas, Emmanouil; Dutton, Susan J.; Patel, Neel; Hawkins, Maria A.; Eccles, Cynthia; Chu, Kwun-Ye; Durrant, Lisa; Abraham, Aswin G.; Partridge, Mike; Woodward, Martha; O'Neill, Eric; et al.
Abstract: Background and purpose: Nelfinavir can enhance intrinsic radiosensitivity, reduce hypoxia and improve vascularity. We conducted a phase II trial combining nelfinavir with chemoradiotherapy (CRT) for locally advanced inoperable pancreatic cancer (LAPC). Materials and methods: Radiotherapy (50.4 Gy/28 fractions; boost to 59.4 Gy/33 fractions) was administered with weekly gemcitabine and cisplatin. Nelfinavir started 3–10 days before and was continued during CRT. The primary end-point was 1-year overall survival (OS). Secondary end-points included histological downstaging, radiological response, 1-year progression free survival (PFS), overall survival (OS) and treatment toxicity. An imaging sub-study ( n  = 6) evaluated hypoxia ( 18 F-Fluoromisonidazole-PET) and perfusion (perfusion CT) during induction nelfinavir. Results: The study closed after recruiting 23 patients, due to non-availability of Nelfinavir in Europe. The 1-year OS was 73.4% (90% CI: 54.5–85.5%) and median OS was 17.4 months (90% CI: 12.8–18.8). The 1-year PFS was 21.8% (90% CI: 8.9–38.3%) and median PFS was 5.5 months (90% CI: 4.1–8.3). All patients experienced Grade 3/4 toxicity, but many were asymptomatic laboratory abnormalities. Four of 6 patients on the imaging sub-study demonstrated reduced hypoxia and increased perfusion post-nelfinavir. Conclusions: CRT combined with nelfinavir showed acceptable toxicity and promising survival in pancreatic cancer.